The lights that failed : European international history 1919 - 1933 - Steiner, Zara 1928-2020 (Oxford history of modern Europe, 2007)
The reconstruction of Europe, 1918-1929. The hall of mirrors : peacemaking in the West -- Distant frontiers : peacemaking in the East -- The missing party : The Soviet Union and the post-war settlements -- The primacy of economics : reconstruction in Western Europe, 1919-1924 -- The primacy of nationalism : reconstruction in Eastern and Central Europe -- Revolution from the right : Italy, 1919-1925 -- The Geneva dream : The League of Nations and post-war internationalism -- New dawn? : stabilization in Western Europe after Locarno -- Faltering reconstruction : cracks in the Locaro fac§ʹade -- Troubled waters : uncertainties in Italy, Eastern Europe, and the Soviet Union -- Faltering internationalism : disarmament and security after Locarno -- Europe reconstructed? -- The hinge years, 1929-1933. The diplomacy of the Depression: the triumph of economic nationalism -- The Manchurian crisis : the european powers and the Far East -- The poisoned chalice : the pursuit of disarmament